Thrombotic Microangiopathy and Acute Kidney Injury Induced After Intravitreal Injection of Vascular Endothelial Growth Factor Inhibitors VEGF Blockade-Related TMA After Intravitreal Use - Hanna, Ramy M.; Tran, Ngoc-Tram; Patel, Sapna S.; Hou, Jean; Jhaveri, Kenar D.; Parikh, Rushang; Selamet, Umut; Ghobry, Lena; Wassef, Olivia; Barsoum, Marina; Bijol, Vanesa; Kalantar-Zadeh, Kamyar; et al. (Frontiers in Medicine, 2020)
Vascular Endothelial Growth Factor (VEGF) inhibition can cause worsening hypertension, proteinuria, chronic kidney injury, as well as glomerular disease. Thrombotic Microangiopathy (TMA) and other nephrotic disorders have been reported with systemic VEGF blockade. These same agents are given intravitreally for age related macular degeneration (AMD) and Diabetic Retinopathy (DR), albeit at lower doses than those given for systemic indications. Systemic absorption of anti-VEGF agents when given intravitreally has been shown consistently along with evidence of significant intravascular VEGF suppression. While worsening hypertension has only been seen in some large-scale studies, case reports show worsening proteinuria and diverse glomerular diseases. These include TMA-associated lesions like Focal and Segmental Glomerulosclerosis with Collapsing Features (cFSGS). In this paper, we report 3 cases of TMA likely associated with the use of intravitreal anti VEGF therapy. These patients developed the signature lesion of VEGF blockade in a 6 month – 11-month time frame after starting intravitreal VEGF inhibitors. The literature is reviewed showing similar cases. Intravitreal VEGF blockade may cause these adverse events in a hitherto unidentified subgroup of patients. Well controlled prospective observational trials are needed to determine the event rate and identify which subgroups of patients are at increased risk. A registry for patients who develop worsening hypertension, proteinuria exacerbation, and glomerular diseases from intravitreal VEGF blockade is proposed.